Lab for Automated Reasoning and Analysis LARA

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
Next revision
Previous revision
sav08:propositional_logic_semantics [2008/03/11 14:51]
vkuncak
sav08:propositional_logic_semantics [2015/04/21 17:30] (current)
Line 8: Line 8:
  
 We next define evaluation function: We next define evaluation function:
-\[+\begin{equation*}
     e : F \to (I \to {\cal B})     e : F \to (I \to {\cal B})
-\]+\end{equation*}
 ++++by recursion on formula syntax tree:| ++++by recursion on formula syntax tree:|
-\[\begin{array}{l}+\begin{equation*}\begin{array}{l}
   e(p)(I) = I(p), \mbox{ for } p \in V \\   e(p)(I) = I(p), \mbox{ for } p \in V \\
-  e({"\lnot "}\> F)(I) = \lnot (e(F)(I)) \\ +  e({'\lnot '}\> F)(I) = \lnot (e(F)(I)) \\ 
-  e(F_1\> {"\land "}\> F_2)(I) = e(F_1)(I) \land e(F_2)(I) \\ +  e(F_1\> {'\land '}\> F_2)(I) = e(F_1)(I) \land e(F_2)(I) \\ 
-  e(F_1\> {"\lor "}\> F_2)(I) = e(F_1)(I) \lor e(F_2)(I) \\ +  e(F_1\> {'\lor '}\> F_2)(I) = e(F_1)(I) \lor e(F_2)(I) \\ 
-  e(F_1\> {"\rightarrow ​"}\> F_2)(I) = (e(F_1)(I) \rightarrow e(F_2)(I)) \\ +  e(F_1\> {'\rightarrow ​'}\> F_2)(I) = (e(F_1)(I) \rightarrow e(F_2)(I)) \\ 
-  e(F_1\> {"\leftrightarrow ​"}\> F_2)(I) = (e(F_1)(I) \leftrightarrow e(F_2)(I))+  e(F_1\> {'\leftrightarrow ​'}\> F_2)(I) = (e(F_1)(I) \leftrightarrow e(F_2)(I))
 \end{array} \end{array}
-\]+\end{equation*}
  
-We wrote symbols like $" ​\land "$ on left in quotes to emphasize that those are syntactic entities, in contrast to symbols like $\land$ on right-hand side that denote propositional operations given by truth tables (stated in [[Propositional Logic Informally]]).+We wrote symbols like $'\land '$ on left in quotes to emphasize that those are syntactic entities, in contrast to symbols like $\land$ on right-hand side that denote propositional operations given by truth tables (stated in [[Propositional Logic Informally]]).
 ++++ ++++
  
Line 29: Line 29:
  
 We denote $e(F)(I) = {\it true}$ by We denote $e(F)(I) = {\it true}$ by
-\[+\begin{equation*}
     I \models F     I \models F
-\]+\end{equation*}
 and denote $e(F)(I) = {\it false}$ by and denote $e(F)(I) = {\it false}$ by
-\[+\begin{equation*}
    I \not\models F    I \not\models F
-\]+\end{equation*}
  
 ===== Validity and Satisfiability ===== ===== Validity and Satisfiability =====
  
 Formula is valid iff $\forall I. I \models F$.  We write this simply Formula is valid iff $\forall I. I \models F$.  We write this simply
-\[+\begin{equation*}
    ​\models F    ​\models F
-\]+\end{equation*}
  
 Formula is satisfiable iff $\exists I. I \models F$ Formula is satisfiable iff $\exists I. I \models F$
 
sav08/propositional_logic_semantics.txt · Last modified: 2015/04/21 17:30 (external edit)
 
© EPFL 2018 - Legal notice